A rare case of retroperitoneal hemolymphangioma. (2018) - Ohsawa, Manato; Kohashi, Toshihiko; Hihara, Jun; Mukaida, Hidenori; Kaneko, Mayumi; Hirabayashi, Naoki
Highlights: Accurate diagnosis of hemolymphangioma preoperatively is difficult. Disease may vary from simple cystic to aggressive lesions, mimicking malignancy. Complete excision provides the best results with a lower recurrence rate. Abstract: Introduction: Hemolymphangioma, a rare vascular developmental condition, is characterized by malformed venous and lymphatic components in various proportions. Herein, we report a case of a retroperitoneal cystic tumor in an adult patient. Presentation of case: A 68-year-old man presented to our hospital with complaints of abdominal pain and vomiting. His abdomen was distended with upper tenderness but without rebound tenderness. Computed tomography (CT) scanning demonstrated a retroperitoneal cystic tumor at the dorsal part of the pancreatic head. Thus, a diagnosis of liposarcoma or lymphoma was made. The patient was scheduled for surgery after his general condition became stable. Intraoperatively, the cystic tumor was found to have originated from the retroperitoneal space. The tumor was in contact with the pancreatic head, abdominal aorta, and inferior vena cava. There was no invasion into the surrounding tissue. The cystic tumor was resected completely. Histopathological examination revealed that the resected retroperitoneal cystic tumor was a hemolymphangioma. The patient had no recurrence during the 12-month follow-up. Discussion: Hemolymphangioma is a rare benign tumor, and its accurate diagnosis before surgery is still difficult. Disease presentation may vary from simple well-defined cystic lesions to aggressive ill-defined lesions, mimicking malignancy. Complete excision provides the best results with a low recurrence rate. Conclusion: Further research is needed on the preoperative radiological diagnosis of such tumors and on how to determine tumor resectability in such cases.